Obtaining L - Glutamate Oxidase Enzyme from Streptomyces and Estimation Its Toxicity on Blood Components - Dina Abdul Hameed; Entesar Ali (Journal of Applied Sciences and Nanotechnology, 2021)
Streptomyces was isolated from the soil and then tested to diagnose morphologically and microscopically. Also, cultivated in the production medium of the L-glutamate oxidase enzyme, for which the wheat bran culture media was used, and then the extracellular L-glutamate oxidase enzyme was extracted using a cooling centrifuge at 8000 rpm for 20 minutes. The optimal temperature and pH for the production of the enzyme’s conditions were studied. Research results revealed that the optimum temperature for enzyme production was 30°C, and the best pH for the enzyme’s production was 7.0 later on, the enzyme was purified using common purification techniques represented by precipitation with ammonium sulfate as a preliminary purification step, followed by dialysis to remove salts, ion-exchange chromatography and gel filtration chromatography were used to finish purification process. The effect of the enzyme toxicity on the human blood components was evaluated. The enzyme had no harmful effect on the blood cells, with Red Blood Cells reaching 4 x 1012, White Blood Cells 7.5 × 109 and Platelets 293 × 109.